Cosmology when living near the Great Attractor - Valkenburg, Wessel; Eggers Bjælde, Ole (Monthly notices of the Royal Astronomical Society, 2012)
If we live in the vicinity of the hypothesized Great Attractor, the age of the universe as inferred from the local expansion rate can be off by 3 per cent. We study the effect that living inside or near a massive overdensity has on cosmological parameters induced from observations of supernovae, the Hubble parameter and the cosmic microwave background. We compare the results to those for an observer in a perfectly homogeneous Λ cold dark matter universe. We find that for instance the inferred value for the global Hubble parameter changes by around three per cent if we happen to live inside a massive overdensity such as the hypothesized Great Attractor. Taking into account the effect of such structures on our perception of the universe makes cosmology perhaps less precise, but more accurate.